2022
DOI: 10.1111/jpm.12829
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric nurse's perceptions of their interactions with people who hear voices: A qualitative systematic review and thematic analysis

Abstract: What is known on the subject?• There is no qualitative systematic review of nurses' perceptions of their interactions with people hearing voices. There are some studies exploring the interventions provided by community psychiatric nurses to people hearing voices; these give a sense of what interactions may contain. What the paper adds to the existing knowledge?• Nurses across both community and inpatient mental healthcare settings feel uncertain about how to interact with people hearing voices, sometimes feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Some argue that the main obstacle to achieving person-centred care relates to concerns of healthcare professionals about risk and decision making capacity of service users ( 58 ) while others have reported that staff (mental health nurses) often feel helpless when faced with individuals presenting with severe mental illness and their interactions with them were influenced by the workplace culture, education and training as well as concern for their own safety ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that the main obstacle to achieving person-centred care relates to concerns of healthcare professionals about risk and decision making capacity of service users ( 58 ) while others have reported that staff (mental health nurses) often feel helpless when faced with individuals presenting with severe mental illness and their interactions with them were influenced by the workplace culture, education and training as well as concern for their own safety ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows several studies focussing on nurses’ or nursing students’ perceptions of the therapeutic relationship with patients [ 5 , 21 ]. However, no studies were found that specifically considered the mentally ill patients’ perspective on this relationship, its importance, and what they expect from nurses concerning their behaviour and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic relationship is not always functional in clinical practice, and there is some discrepancy between the ideals of mental health nursing and actual practice in the form of reduced availability and accessibility. The therapeutic relationship may be negatively influenced by various factors, such as lack of time, lack of job motivation, exhaustion and rejection towards the person cared for (Hem & Heggen, 2004, Moreno‐Poyato et al, 2016, McCluskey et al, 2022). Rejection is reflected in clinical practice as distance, which can be helpful in maintaining the service user's dignity, but it could also appear as a result of personal dislike (Hem & Heggen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic relationship has been defined as the cornerstone of mental health practice and pivotal to recovery‐oriented mental healthcare (McCluskey et al, 2022). The views of the therapeutic relationship seem to be similar both for nurses and mental health service users, framed as one‐party wishing to help and the other to be helped, and resting on trust and respect (Moreno‐Poyato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation